3t-6=4t+12

Simple and best practice solution for 3t-6=4t+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3t-6=4t+12 equation:


Simplifying
3t + -6 = 4t + 12

Reorder the terms:
-6 + 3t = 4t + 12

Reorder the terms:
-6 + 3t = 12 + 4t

Solving
-6 + 3t = 12 + 4t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-4t' to each side of the equation.
-6 + 3t + -4t = 12 + 4t + -4t

Combine like terms: 3t + -4t = -1t
-6 + -1t = 12 + 4t + -4t

Combine like terms: 4t + -4t = 0
-6 + -1t = 12 + 0
-6 + -1t = 12

Add '6' to each side of the equation.
-6 + 6 + -1t = 12 + 6

Combine like terms: -6 + 6 = 0
0 + -1t = 12 + 6
-1t = 12 + 6

Combine like terms: 12 + 6 = 18
-1t = 18

Divide each side by '-1'.
t = -18

Simplifying
t = -18

See similar equations:

| 8/10=12/x | | 3x+7=-28-4x | | (x-3)^2/3=0 | | a/6+8=11 | | 80=8*10 | | 10+5x=-6+x | | 8/12=x10 | | 10+5x=16x-54 | | t/6-4=10 | | (4x+132)+(6x+38)=180 | | 72=8*9 | | Ln(x-49)=3 | | 9h-22=50 | | p(x)=x^2-144 | | x^2+95x+2100=375 | | -22+(-10)+15= | | 2(q+2)+3=-26 | | 6n-85=36 | | 56=8*7 | | -n^2-14n=o | | 2/5/x=2/0.6 | | -14+0+13= | | a/4+6=11 | | (x+2)+(2x)=140 | | x=35y=33 | | 4x-10=3x+6 | | t-30=1 | | 2y+11=-4+7 | | p^2+3p=p(p+4) | | t/5-1=14 | | Log(9x-7)-Log(x-5)=1 | | 6y-5x=2 |

Equations solver categories